THE EFFICACY OF PROBLEM-BASED LEARNING IN DEVELOPING ETHICAL-DECISION MAKING AND CRITICAL THINKING SKILLS IN 6TH GRADERS - Klaus Müller; Anna Weber; Maxime Berger (International Journal of Educatio Elementaria and Psychologia, 2025)
The growing emphasis on fostering critical thinking and ethical decision-making skills in education has led to the exploration of various teaching methodologies. Problem-Based Learning (PBL), an instructional strategy that involves students solving complex, real-world problems, has gained attention for its potential to enhance both of these competencies. However, there is limited research on the effectiveness of PBL in developing ethical decision-making and critical thinking skills in primary school students. This study aims to assess the efficacy of PBL in developing these skills in 6th-grade students. A mixed-methods approach was used, combining quantitative pre- and post-assessment scores with qualitative data from interviews and classroom observations. The experimental group, consisting of 6th graders who engaged in a PBL curriculum, showed a significant increase in both ethical decision-making and critical thinking skills compared to the control group. Statistical analysis revealed that the experimental group’s improvement was statistically significant (p < 0.05). The study concludes that PBL is an effective pedagogical tool for developing ethical decision-making and critical thinking skills in young learners. The findings suggest that PBL encourages students to engage in reflective thinking, explore ethical dilemmas, and apply critical analysis to real-world issues. Future research should further explore the long-term impact of PBL on these skills and investigate its application across different age groups and educational settings.